Location, location, location! Rewiring IL‐2 circuits defines context‐specific outcomes. Issue 8 (5th August 2022) - Rankin, Lucille; Gray, Daniel
Abstract : Here, we highlight a recent publication by Whyte et al. that reveals diverse immune outcomes of interleukin (IL)‐2 expression in distinct microenvironments. Their definition of context‐dependent IL‐2 networks paves the way for the development of tissue‐specific therapies that enlist the potent immuno‐modulatory activity of IL‐2.